Gender role changes and their impacts on Syrian women refugees in Berlin in light of the Syrian crisis - Nisren Habib (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2018)
Gender roles of Syrian women started to shift in 2011, in light of the Syrian conflict. This shift was a response to the difficult situations which Syrian women faced inside Syria as well as in the neighboring countries to which they fled in the attempt to find safer living conditions. However, the uncertain situation and the precarious working and living conditions in Syria and the neighboring countries forced many Syrian women and families to flee to Europe, with the highest number to Germany, facing the challenge of a new culture and new social norms. The main purpose of this study is to evaluate if and how the gender roles of Syrian women who fled to Berlin, Germany, have shifted. Using semi-structured interviews conducted in the period July - December 2016, the study illustrates the challenges and opportunities they face, both as women and as refugees, and in how far these affect their gender roles.
Keywords: 300; Gender roles changing; Refugees; Integration